Sawdust as an Organic Amendment on Uptake of Herbicide Residues by Amaranthus dubius in Contaminated Soil - Sanjo Abolarin; Maina Mam Ago (Journal of Chemistry Letters)
Herbicide use and varieties have greatly risen during the past few years. As a result of this, concern over potential health effects such cancer, birth deformities, reproductive issues, tumours, and harm to the liver, kidneys, and nervous system is on the rise. This has an impact on the environment because the misuse of herbicides contaminates the soil, water, and air; harming the local ecology and other living things vital to preserving ecological balance. This study investigated the effect of sawdust as an organic amendment on mobility of herbicides residues in contaminated soil, in which Chinese Spinach (Amaranthus dubius) was grown. Sawdust of Doka (Isoberlinia doka), African Mahogany (Khaya senegalensis) and Beach Wood (Gmelina arborea), were used in a randomized complete block design. A composite sample of topsoil (110 kg) and sawdust compost (10kg) was used. 120kg of topsoil without sawdust compost was also used as control. Amaranthus dubius was planted in the potted mixtures and 120ml of herbicide (Glyphosate 41% SL) was diluted with 5 litres of water and was applied to all treatment at an equal rate after sowing. Gas Chromatography Mass Spectroscopy (GCMS) analysis of the active ingredient in the glyphosate 41% SL indicated that the quantity of Isopropylamine was 34.093ppm. The highest mean of Isopropylamine (32.75ppm) was found in the control treatment without sawdust amendment, as compared with other samples. The chemical herbicide was detected, at negligible rates, in Amaranthus dubius grown in the soil amended with Gmelina arborea (10.49ppm) and Khaya Senegalensis (8.93ppm). The concentrations in Amaranthus dubius from the two amended soils were significantly lower than that of the control (22.56ppm) without compost treatment. However, no herbicide was detected in the vegetable raised on soils amended with compost made from Isoberlina doka specie.